Intersectional inequalities in mental health by education, income, gender, and age before and during the COVID-19 pandemic in the Netherlands: a longitudinal study - Sanne E. Verra; Clare Evans; Joost Oude Groeniger; John de Wit; Maartje P. Poelman; Carlijn B. M. Kamphuis (International Journal for Equity in Health)
Abstract Background It remains unclear how COVID-19 has disproportionately affected the mental health of different vulnerable groups. This study explores how mental health inequalities changed between 2014 (pre-COVID-19) and 2021 (during COVID-19) in the Netherlands across intersectional social strata defined by interplays of educational attainment, income level, gender, and age. Methods Using 2014 and 2021 self-reported cohort data on health and living conditions of the adult population of Eindhoven and surroundings (N = 1,157), a Multilevel Analysis of Individual Heterogeneity and Discriminatory Accuracy (MAIHDA) was applied to explore intersectional inequalities in mental health in 2014, 2021, and in mental health changes (2014–2021). We examined this using the Mental Health Inventory-5 across 53 intersectional social strata based on interplays of education, income, gender, and age in 2014. Results There were substantial differences in mental health trajectories across social strata. Between-stratum mental health inequalities were patterned additively, indicating that inequality patterns along one axis (such as income) tended to be consistent across other axes of comparison. Additive trends revealed that women with a low income were at highest risk of poor mental health in 2014 and 2021, and people over 65 were at highest risk of mental health setbacks over time. Nonsignificant educational inequalities were found in 2014 and 2021. Income inequalities persisted, but slightly decreased in 2021 due to stronger mental health setbacks among those with high incomes. Women experienced persisting disadvantages that slightly flattened over time, and the mental health advantages of older age diminished over time. Conclusions Inequalities in mental health add up for those who experience multiple axes of disadvantage, such as women and those with low incomes, but no disproportionate intersectional interaction effects were found. Effort is needed to ensure that mental health support is accessible for all, especially those with low incomes. Given the especially strong mental health declines among those over 65, responses to future crises need to include measures to protect the mental health of the elderly. Future research should investigate intersectional inequalities along other axes of disadvantage, such as ethnicity, employment and family status.